Pengaruh Terapi Mindset terhadap Peningkatan Perilaku Disiplin Penerima Manfaat di Satuan Pelayanan Griya Ramah Anak Bogor - Sari, Nilah Wati Indra Nur Meinda Sari; Tukino, Tukino; Setianingsih, Krisna Dewi (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2023)
The presence of individual cognitive distortions can affect the motives for undisciplinary behavior. The study aims to obtain an empirical view of the impact of the implementation of engineering therapy results–Mindset therapy (Motivational Interviewing and The Decision Fostering Intervention) on the improvement of disciplinary behavior. The subjects of the study were beneficiaries in the Satuan Pelayanan Griya Ramah Anak Bogor, three teenagers aged 16 – 17 who had problems with undisciplinary behavior. Non-disciplinary behavior is the behavior of not following the activities of worship, sleeping during social guidance, and not following the evening learning activities. The research uses a quantitative approach to the single subject design method with an A-B-A reversal design. Data collection using observation techniques, questionnaires, interviews, and documentation studies. The validity test of the questionnaire uses face-to-face validity tests and statistics. The reliability test uses the alpha-Cronbach statistical test, while the recording of events is done by calculating percentage agreement. The results of the study showed that Mindset therapy influenced a decrease in targeted behavior, thus indicating an improvement in the disciplinary behavior of the three research subjects. This is demonstrated through the tendency of graph orientation and data analysis results, as well as the presence of increased questionnaire response scores between before and after interventions of three research subjects.